Legal Issues in the Monitoring and Enforcement of the National Strategy under the Constitution of the Kingdom of Thailand and the National Strategies Preparation Act, B.E. 2560 (2017) - Boonkiatsakul, Chalermchon (Journal of Thai Ombudsman, 2026)
This article examines the status, roles, and legal effects of the National Strategy under the Constitution of the Kingdom of Thailand B.E. 2560 (2017) and the National Strategy Preparation Act B.E. 2560 (2017). The study analyzes the relationship between the National Strategy and relevant public law frameworks, including laws governing public administration, administrative procedure, budgeting, fiscal discipline, public procurement, state audit, and anti-corruption measures, in order to assess the extent to which these mechanisms can supervise, monitor, and ensure that state agencies operate in accordance with the National Strategy. The study also employs a comparative approach by examining the legal frameworks of the Republic of Korea, the Republic of Singapore, and the United Kingdom. This research adopts a documentary methodology based on the analysis of legislation, academic literature, and official governmental documents. The findings indicate that, although the National Strategy has been elevated as a binding framework for public administration and is supported by various legal mechanisms relating to public administration, budgeting, fiscal management, and public accountability, the relationship between such mechanisms and the monitoring and evaluation system established under the National Strategy Preparation Act B.E. 2560 (2017) remains insufficiently articulated. In particular, greater clarity is needed regarding the use of evaluation results in budgetary consideration, administrative supervision, and the determination of accountability for state agencies. Furthermore, the enforcement of Section 26 remains subject to practical limitations due to the ambiguity of certain legal terms and the evidentiary burden associated with its application. The study therefore proposes strengthening the coherence of the monitoring framework, improving the integration of evaluation outcomes into administrative and budgetary processes, developing accountability measures appropriate to the nature of public policy governance, and enhancing the transparency, continuity, and effectiveness of monitoring and evaluation mechanisms. These measures would contribute to a more effective implementation of the National Strategy in practice.